Investigation of spectroscopic and thermo-mechanical behaviors of different phenanthroimidazole-azo dyes in solvent and polymer medium - Seçil Çelik Erbaş; Umut Uregil; Sibel Gülle; S Bahar Baştürk (Materials Research Express, 2020)
The aim of this study is the investigation of the interaction between dyes and polymers which have different polarities. Dye doped polymer films have larger application areas because of the fact that dye is more stable when doped in polymer compared to solvent medium. However, dye dispersion in the polymer medium affects both the spectroscopic and mechanical properties of the polymer. The polymer-dye interaction must be high for a good dispersion,. In this study, polypropylene with apolar character and polymethylmethacrylate with polar groups were chosen as a solid phase to examine polymer-dye interactions. The photophysical properties of phenanthroimidazole-azo compounds synthesized previously were examined with UV–visible and fluorescence spectroscopy techniques in tetrahydrofuran and two polymer media. Also, photostability tests of azo dyes in THF and polymer films were performed. Surface roughness characterizations of polymer films were carried out with AFM. Additionally, the viscoelastic behaviors of the polymethylmethacrylate and polypropylene films under sinusoidal vibrations at different temperatures were studied by dynamic mechanical analysis technique.